Oropharyngeal Dysphagia in Mucopolysaccharidoses: Evidence from Videofluoroscopic Swallowing Study - Luciana Carneiro; Carolina F.M. Souza; Roberto Giugliani; Simone C. Fagondes (Journal of Inborn Errors of Metabolism and Screening, 2022)
Abstract Mucopolysaccharidoses (MPS) are rare inborn errors of metabolism, leading to the accumulation of glycosaminoglycans (GAG) in distinct tissues. We investigated oropharyngeal dysphagia using the videofluoroscopic swallowing study (VFSS) in patients with different MPS types. Since there is a lack of studies systematically evaluating this disorder in this population, the use of a standard technique should contribute to better evaluate individuals with MPS. A cross-sectional and observational study enrolling patients followed by an outpatient service for lysosomal diseases at the Genetics Service of the Hospital de Clínicas de Porto Alegre (SGM/HCPA) was conducted. Patients underwent semi-structured interviews, clinical evaluation and VFSS. Nineteen patients were evaluated, including patients with MPS types I (16%), II (42%), IIIb (10%) and IVa (32%). Nearly all patients (95%) presented with oropharyngeal dysphagia in the VFSS. The most frequent findings were impaired chewing during oral phase (94%) and reduced laryngeal elevation in the pharyngeal phase (72%). Oropharyngeal dysphagia constituted a prevalent symptom in the studied cohort regardless of MPS type. Our data reinforces the notion that this disorder should be objectively assessed since it can significantly compromise the nutrition and the hydration of these patients as well as lead to tracheobronchial aspiration, thus resulting in aspiration pneumonia and even death eventually.